Awaiting absolution – self-presentations in letters of application for debt reconstruction. Issue 1 (2nd January 2022) - Liedgren, Pernilla; Kullberg, Christian
ABSTRACT: The article investigates how over-indebted persons present their case in personal letters attached to debt-reconstruction applications and how their narratives can be argued to contain features that help counteract negative expectations about their identity. The results reveal three types of narratives. These are: negotiating, in which the applicant communicates personal agency in relation to all areas of life, and the promise to start a new life and continue on the path of improvement is invoked as the main reason for being deserving of help; reimbursement-claiming, in which personal agency is communicated in relation to all aspects except for the applicant's personal economy, and earlier achievements are invoked as the main reason for being deserving of help; and confessing, in which personal agency is communicated as located outside the applicant's control, and a lack of possibilities to manage one's own personal economy is invoked as the main reason for being deserving of help. The results also show that, although all three narrative categories can be considered counter-stories, confessing can be argued to have the greatest potential to counteract negative expectations and thereby help to repair the applicant's identity.